2021
DOI: 10.3390/ijerph18031124
|View full text |Cite
|
Sign up to set email alerts
|

College Students’ Views on Functional, Interactive and Critical Nutrition Literacy: A Qualitative Study

Abstract: This research aimed to uncover how the nutrition literacy domains (functional, interactive, critical) influence the dietary decisions of young adults in college. For this qualitative study, undergraduate college students aged 18–24 years old (n = 24) were recruited to participate in focus groups. The focus group transcripts were independently coded for primary and secondary themes using a grounded theory approach and a basic thematic analysis. Four focus groups with 5–7 participants per group were conducted. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
1
8
0
1
Order By: Relevance
“…This could be overestimated and misleading as guidelines to healthy diet have other aspects such as intake of fruits and vegetables and lower intake of soft drinks among others, which is in accordance with what was found previously (17,19). For example the score for con dence on the de nition of healthy diet was high, whereas the knowledge of WHO guidelines on healthy nutrition was low, which indicate that the participants may have overestimated their skills with regards to nutrition knowledge.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This could be overestimated and misleading as guidelines to healthy diet have other aspects such as intake of fruits and vegetables and lower intake of soft drinks among others, which is in accordance with what was found previously (17,19). For example the score for con dence on the de nition of healthy diet was high, whereas the knowledge of WHO guidelines on healthy nutrition was low, which indicate that the participants may have overestimated their skills with regards to nutrition knowledge.…”
Section: Discussionsupporting
confidence: 83%
“…Also, participants who had higher level of FNL seemed to trust resources of nutrition information such as doctors, nurses, books and internet. Previous literature supports positive association between diet behavior and nutrition literacy (16,17). So one can conclude that improved nutrition literacy could prevent chronic diseases (18).…”
Section: Discussionmentioning
confidence: 59%
“…We observed that in the initial academic year, the study sample showed a statistically higher alcohol consumption weekly (1-4 times/week) (27.3%) with a relatively high 5-6 times/week and everyday alcohol consumption (3.4% and 2.9%, respectively), probably due to peer influences [24]. In the following years, the frequent alcohol consumption habit (more than 1-4 times per week) decreased, probably due to high academic assignments; however, in the sixth year, the study reveals the highest daily alcohol consumption (6.5%), suggesting a possible progressively developed increased addictive behavior due to environmental factors during university years.…”
Section: Alcohol and Illicit Drug Abusementioning
confidence: 73%
“…Furthermore, participants with a higher level of FNL appeared to trust nutrition information sources such as doctors, nurses, books, and the internet. Previous research has found a link between diet behavior and nutrition literacy [ 23 , 24 ]. As a result, improved nutrition literacy may help to prevent chronic diseases [ 25 ].…”
Section: Discussionmentioning
confidence: 99%